2010
DOI: 10.1016/j.bcmd.2009.12.010
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs expression signatures are associated with lineage and survival in acute leukemias

Abstract: MicroRNAs (miRNAs) are small (~22 nucleotide) non-coding RNAs whose altered expression has been associated with various types of cancers, including leukemia. In the present study, we conducted a quantitative PCR (qPCR) analysis of expression of 23 human precursor miRNAs in bone marrow specimens of 85 Chinese primary leukemia patients, including 53 acute myeloid leukemia (AML) and 32 acute lymphoblastic leukemia (ALL) cases. We show that 16 miRNAs were differentially expressed between AMLs and ALLs; Of them, ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
122
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(132 citation statements)
references
References 51 publications
5
122
1
4
Order By: Relevance
“…Of particular interest from this group is miR-222, miR-221 and miR223, which have been shown to be highly expressed in AML compared with other leukaemias. 37 Moreover, we also noted that high NRF2 activity caused a decrease in the expression of miRNAs, which includes miR-154, miR146a and miR-181B. All these miRNAs have been shown to be of interest in AML with miR-146a being shown to have low expression in AML, which correlates with high expression of its target gene CXCR4, 38 which in a separate study has been shown to be regulated by NRF2 in human HSC.…”
Section: Discussionmentioning
confidence: 67%
“…Of particular interest from this group is miR-222, miR-221 and miR223, which have been shown to be highly expressed in AML compared with other leukaemias. 37 Moreover, we also noted that high NRF2 activity caused a decrease in the expression of miRNAs, which includes miR-154, miR146a and miR-181B. All these miRNAs have been shown to be of interest in AML with miR-146a being shown to have low expression in AML, which correlates with high expression of its target gene CXCR4, 38 which in a separate study has been shown to be regulated by NRF2 in human HSC.…”
Section: Discussionmentioning
confidence: 67%
“…After manually screening the titles, abstracts and key data, 259 records were excluded for not meeting the criteria listed above. Of the 28 reports selected for the systematic review, 12 studies were excluded in the final meta-analysis for lack of key HR value [21][22][23][24][25][26][27][28][29][30][31][32]. The excluded 12 studies commonly focused on other miRNAs and did not analyze the miR-155 data individually.…”
Section: Resultsmentioning
confidence: 99%
“…Down-regulation of miR-146a expression by the c-Myc oncogenic transcription factor has been previously observed in human and mouse B-cell lymphomas (30). Recent studies have evaluated the expression levels of miR-146a in acute lymphocytic leukemia and chronic lymphocytic leukemia (31)(32)(33). Their findings imply that miR-146a expression involved in deletion or amplification may be cell type-specific.…”
Section: Mir-155 and Mir-146a As Diagnostic Tools In Dlbcl Patientsmentioning
confidence: 93%